Insight into an Integrated Evaluation of Unmitigated Disposal Options for the Largest Waste Disposal Site in Tehran Using Rapid Impact and Sustainability Assessment Method - Ali Daryabeigi Zand; Maryam Rabiee Abyaneh (Avicenna Journal of Environmental Health Engineering, 2021)
This study integrated the rapid impact assessment matrix (RIAM) analysis and the mathematical sustainability modeling to evaluate disposal options so as to find the most appropriate and practical unmitigated option for the main waste disposal site in Tehran, Iran. RIAM analysis was used to assess environmental impacts of five potential disposal options followed by determination of sustainability for each option. RIAM analysis results indicated that option 5 (i.e., composting) had the least negative cumulative impacts on the environmental score value of -481 among the studied options. Incineration of wastes, option 4, was found to be the least favorable option mainly due to the high relevant costs and emission of air pollutants. Option 3, sanitary landfilling, was found to have fewer negative impacts compared to the options 1 (open dumping), 2 (land burial), and 4. It was also found that none of the examined options were sustainable in unmitigated state; however, results indicated that option 5 was the most favorable one in terms of sustainability with an obtained sustainable value of -0.126, which was the lowest value of unsustainability found in the present study. Calculated values of environment for the evaluated options in unmitigated state were not sufficient enough to compensate for the corresponding values of human needs and interests. Finally, option 5 followed by option 3 were suggested as alternative disposal approaches for the current methods in unmitigated state to reduce negative environmental impacts of waste disposal.